The portal of the mystery of hope - Péguy, Charles (Ressourcement (Grand Rapids, Mich.), 2005)
Translated by David L. Schindler, JrIn what is one of the greatest Catholic poetic works of our century, Peguy offers a comprehensive theology ordered around the often-neglected second virtue which is incarnated inhis celebrated image of the 'little girl Hope